NMAM Methods Update: A Laboratory Response to Concerns About Technologically Outdated and Problematic Methods - Pendergrass, Stephanie M.; Ernst, Jennifer L.; Dollberg, Donald D. (Journal of occupational and environmental hygiene, 2006)
The National Institute for Occupational Safety Health (NIOSH) publishes the NIOSH Manual of Analytical Methods (NMAM). The NMAM, although subject to various revisions and the incorporation of supplemental editions over the years, still contains many methods that are technologically outdated or problematic, as identified in a recent survey of the various users of the NMAM. Whereas the survey identified a number of problematic methods based on various chromatographic techniques, those selected for inclusion in this project employed analysis by gas chromatography (GC). The GC methods selected for evaluation were categorized as Phases 1, 2, 3, and 4 based on necessity as determined by the results of the client survey or internal assessment. The Phase 1 methods included: NMAM 1606 (Acetonitrile), NMAM 2005 (Nitroaromatic Compounds), and NMAM 1453 (Vinyl Acetate); the Phase 2 methods: NMAM 1003 (Halogenated Hydrocarbons), NMAM 1501 (Aromatic Hydrocarbons), NMAM 2555 (Ketones I), and NMAM 1403 (Alcohols IV); the Phase 3 methods: NMAM 2552 (Methyl Acrylate), NMAM 2537 (Methyl and Ethyl Methacrylate), and NMAM 2553 (Ketones II), and the Phase 4 methods: NMAM 2556 (Isophorone), NMAM 1460 (Isopropyl Acetate), and NMAM 1618 (Isopropyl Ether). All methods previously specifying packed column chromatography have been evaluated using the appropriate fused silica capillary column. Improvements in individual analyte desorption efficiencies were achieved at concentrations substantially lower than those used in the previous methods. Most analytes evaluated had their respective limit of detection lowered by a factor of ten-to twentyfold. Thirty-day storage stability studies, previously lacking in a number of methods or for new analytes, were successfully completed to meet current method development criteria. Additional benefits resulting from this effort included the incorporation of single analyte methods into chemically related multianalyte methods and the evaluation of certain isomers, such as the methylstyrenes and xylenes, which previously could not be separated.